Kainuun saamelaisperäisiä paikannimiä - Räisänen, Alpo (Kotikielen Seura, 1995)
Kainuu place-names of Saami origin (englanti)1995 (99)Alpo Risnen (University of Joensuu; Department of Finnish; address: PL 111, FIN-80101 Joensuu)Kainuu place-names of Saami origin The writer has earlier discussed Kainuu place-names that date from before the present settlement in the area (Risnen 1990). The present settlement of Kainuu dates from the 16th and 17th centuries, and came mainly from Savo. In the previous study, three strata were distinguished in the older place-names: (1) Saami names, (2) Karelian names, and (3) Ostrobothnian names.The present article discusses additional Kainuu place-names that the writer argues to be of Saami origin. In addition to linguistic factors, particular attention is paid to the naming motive, i.e. the actual nature of the places referred to. For example, names with the form ntti- in Kainuu and n- and nkk- in East Finland often mean large lakes or bodies of water. These names can thus be linked to the Saami word dne- 'big' (compare Finnish en-). The four Finnish Jaappa(a) names denote bodies of water. They can be related to the Saami word cap'pd 'black' (cf. Nielsen), because the colour of the water or the shadow of the surrounding forest often motivated such Finnish names as Mustalampi 'black pool' and Mustalahti 'black bay'. There are about 40 names in Finland of the form Laatas, Laattaa, and they all originate in the Saami adjective lhtes 'level'. The Laattaa-names in North Savo and Kainuu nevertheless require the original form *laattaga, so they cannot come directly from the Saami form lhtes but from its g-form derivative.Of particular interest are the two Juolunka names in Kuhmo and the Juolu names in Central Ostrobothnia and western Lapland, whose source is Saami cuollo 'salmon-dam bar, fence'. Both the Kuhmo names originally denoted a long, narrow peninsular between two lakes. In Central Ostrobothnia Juolu often means a narrow sandy ridge. Such sites were good places to trap wild deer. This evidence from place-names confirms the suggestion made by A. Nesheim ...